Ignition enhancement of lean propane/air mixture by multi-channel discharge plasma under low pressure. (5th February 2019) - Lin, Bingxuan; Wu, Yun; Zhang, Zhibo; Bian, Dongliang; Jin, Di
Graphical abstract: Highlights: Concentrated and distributed multi-channel spark discharge (MSD) is proposed. The evolution of multi-channel discharge is designed and analyzed. Concentrated MSD can enhance ignition to flame transition under lower pressure. Concentrated MSD has little influence on the subsequent flame propagation. Abstract: Ignition enhancement in a lean-burn combustor under low pressure is the biggest challenge for high altitude long endurance aircraft. In this study, plasma-assisted ignition using multi-channel spark discharge is proposed according to the theory of critical flame radius (Rc ). A time-phased breakdown method is adopted to separate the breakdown stage from the discharge. The arc stage is restrained to reduce energy loss and maintain high voltage. Ignition experiments using single-channel spark discharge (SSD), concentrated multi-channel spark discharge (MSD) and distributed MSD were conducted. The results showed that Rc is crucial for the ignition. The ignition probability of SSD drops quickly as pressure decreases due to the requirement of a larger Rc . The enhancement of concentrated MSD ignition is obvious at the same initial pressure than that of SSD and distributed MSD. The ignition enhancement is obtained only when the multi-channel combines to create a much larger ignition kernel and exceeds Rc easily. Still, the ignition capability of MSD at extremely low pressure with lean and stoichiometric mixture does not perform as expected due to the splitting of the flame kernel. MSD can enhance ignition to flame transition but has little influence on the subsequent flame propagation.